O PARCELAMENTO DO CRÉDITO TRIBUTÁRIO E SUAS REPERCUSSÕES NOS CRIMES TRIBUTÁRIOS MATERIAIS - Giacomolli, Nereu José; Saibro, Henrique (Revista da AJURIS, 2021)
THE TAX CREDIT INSTALLMENT AND ITS REPERCUSSIONS IN TAX CONSUMMATE OFFENSES ÁREA(S): Direito penal tributário; direito processual penal. RESUMO: Este estudo analisa quais são os efeitos que o parcelamento, por meio da suspensão da exigibilidade do crédito tributário, trará à imputação penal, quando se tratar de persecutio criminis envolvendo o cometimento de crime material contra a ordem tributária. Esta abordagem se divide em três partes, partindo das características peculiares do parcelamento, dentro do ordenamento jurídico. O artigo também se volta ao arcabouço normativo acerca do parcelamento tributário e de seus efeitos criminais. Ao final, por meio de uma pesquisa jurisprudencial, a investigação problematiza acerca da temporalidade legal a incidir nas hipóteses de parcelamento: data dos fatos ou data do acordo. O objetivo principal é responder quais são, efetivamente, as hipóteses de parcelamento do crédito tributário que produzem efeitos na imputação penal tributária. ABSTRACT: This study analyzes the effects of the installment through the liability suspension of the tax credit in the criminal imputation when dealing with persecutio criminis involving tax consummate offenses. For this, the article is divided into three parts. The first deals with the peculiar characteristics of the installment within the legal system, including its repercussion beyond the Criminal Law. The other focus of the research turns to the set of laws that deals with the installment and its different statutory provision as to its consequences in the criminal sphere. Concurrently, the jurisprudence on the subject is analyzed. Finally, through a jurisprudential research, in case of installment it is examined if the application of the law is the prevailing by the time of the accession of the agreement or at the time of the facts. It is intended to gather and to expose what are the tax credit installment hypotheses that effects the criminal imputation, on the basis what provides each governing law and jurisprudence about the tax liability. PALAVRAS-CHAVE: Crimes contra a ordem tributária; parcelamento; suspensão da exigibilidade; efeitos. KEYWORDS: Tax crimes; liability installment; liability suspension; effects. SUMÁRIO: Introdução; 1 O parcelamento no ordenamento jurídico brasileiro; 2 A normatização por meio da Lei nº 9.249/1995 e o seu questionamento jurisprudencial; 3 A normatização por meio da Lei nº 9.964/2000 (Refis) e o seu questionamento nos Tribunais; 4 A normatização da Lei nº 10.684/2003 (Refis II ou Paes) e a problematização na jurisprudência; 5 A previsão legislativa na Lei nº 11.941/2009 (Paex e Refis IV) e a manifestação dos Tribunais; 6 A normatização na Lei nº 12.382/2011; 7 Incidência da lei vigente à época dos fatos ou da adesão ao parcelamento; Conclusão; Referências. SUMMARY: Introduction; 1 The installment in the Brazilian legal system; 2 The normative regulation through Act 9.249/1995 and its jurisprudential questioning; 3 The normative regulation through Act 9.964/2000 (Refis) and its jurisprudential questioning; 4 The normative regulation through Act 10.684/2003 (Refis II or Paes)) and its jurisprudential problematization; 5 The statutory provision in Act 11.941/2009 (Paex e Refis IV) and Court’s manifestation; 6 The normative regulation in Act 12.382/11; 7 Incidence of the law in force at the time of the facts or of installment’s adhesion; Conclusion; References.